Analysis the Factor of Customer Satisfaction in Service Business (Case of Spa Business) - Putri, Marcha Monita Ayu; Rachmawati, Evy (Journal of Innovation, Business and Entrepreneurship, 2016)
Abstract. The purpose of this research is to basically identify which factors affects customer satisfaction after receiving a spa service treatment, thus later could produce a good recommendation for a similar business from the result of the research. Previous research shows there are four factors which affects customer satisfaction in spa services, which are service quality; perception towards the spa; perception towards the price; and perception towards the therapist. The respondents in this research are women who are aged between 18 to 50 years old and are currently living in Bandung and its surrounding area. The author uses questionnaire to obtain primary data and literature studies to obtain secondary data. Multiple linear regression is used for analyzing the connection between customers response and their satisfaction after having spa activity with the factors affecting it. The result of data analysis shows that from four factors that affect customer satisfaction, there are three factors that influence the customer satisfaction and one one factor that does not influence customer satisfaction. Result from the data analysis reveals that the perception of price is the most influencing factors because it has the biggest t-score in the t-test result (table 1.1). While perception of store is the one that not affect customer satisfaction because the t-score is less that t-table, therefore, the hypotheses is rejected. The other factors that influencing the customer satisfaction are perception of employee for the second and then the service quality for the third.Â Keywords: Customer Satisfaction, Service Business, Spa Business